THE INFLUENCE OF TRUST, CONVENIENCE AND PRODUCT DIVERSITY ON PURCHASE DECISION OF TOKOPEDIA CLOTHING PRODUCT (A STUDY ON STUDENTS OF IBA BATCH 2016 FACULTY OF ECONOMICS AND BUSINESS) - Octaviani Meisy Tirsa Bogia (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
Abstract: The purpose of this study is to find out the influence of trust, convenience, and product diversity towards purchase decision. The research Methodology used is descriptive using multiple linear regression test. 47 samples were collected with questionnaire distributed to students of IBA Batch 2016. The conclusion on this study were (1) trust partially influence positive and significant relathionship with purchase decision. (2) convenience partially influence positive and significant relationship with purchase decision (3) product diversity influence partially positive and significant relationship with purchase decision.(4) trust, convenience, and product diversity is simultaneously influence the purchase decision.Keywords: trust, convenience, product diversity, purchase decision.